2020
DOI: 10.1093/mnras/staa469
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle of the Central Molecular Zone – II. Distribution of atomic and molecular gas tracers

Abstract: We use the hydrodynamical simulation of our inner Galaxy presented in Armillotta et al. (2019) to study the gas distribution and kinematics within the CMZ. We use a resolution high enough to capture the gas emitting in dense molecular tracers such as NH 3 and HCN, and simulate a time window of 50 Myr, long enough to capture phases during which the CMZ experiences both quiescent and intense star formation. We then post-process the simulated CMZ to calculate its spatially-dependent chemical and thermal state, pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 94 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…In contrast, the default particle mass in Armillotta et al (2019) is 2000 M , a factor of 1000 worse than we achieve here. Armillotta et al (2019) and Armillotta, Krumholz & Di Teodoro (2020) also present results from a 'high-resolution' run with a particle mass of 200 M , which they carried out for a much shorter period than their main run, but even this has a much worse resolution than our simulation. An important consequence of this difference in resolution is that in the Armillotta et al (2019) simulation, the Sedov-Taylor phase following an SN explosion is resolved only for SNe exploding in low-density gas with n < 1 cm −3 , whereas in our simulation it remains well resolved even for SNe exploding in gas with a density close to our sink creation threshold.…”
Section: What Drives the Time Variability Of The Sfr In The Cmz?mentioning
confidence: 77%
“…In contrast, the default particle mass in Armillotta et al (2019) is 2000 M , a factor of 1000 worse than we achieve here. Armillotta et al (2019) and Armillotta, Krumholz & Di Teodoro (2020) also present results from a 'high-resolution' run with a particle mass of 200 M , which they carried out for a much shorter period than their main run, but even this has a much worse resolution than our simulation. An important consequence of this difference in resolution is that in the Armillotta et al (2019) simulation, the Sedov-Taylor phase following an SN explosion is resolved only for SNe exploding in low-density gas with n < 1 cm −3 , whereas in our simulation it remains well resolved even for SNe exploding in gas with a density close to our sink creation threshold.…”
Section: What Drives the Time Variability Of The Sfr In The Cmz?mentioning
confidence: 77%
“…Moreover, reproducing the KDL orbit would require that a sequence of clouds are launched with exactly the same initial conditions from the same point in space during a time interval of 5 Myr, which is unlikely to happen given the stochastic nature of the perturbations. Armillotta et al (2020) also report that they are unable to reproduce a stream with the characteristics of the KDL orbit in their simulations. At present, it remains to be shown that excursions compatible with the KDL orbit can occur in a self-consistent simulation of gas flow in a barred potential.…”
Section: Orbits Versus Open Orbit: a False Dichotomy?mentioning
confidence: 99%
“…Molinari et al 2011;Immer et al 2012Immer et al , 2016Jones et al 2012;Ginsburg et al 2016;Henshaw et al 2016;Kauffmann et al 2017a, b;Krieger et al 2017;Longmore et al 2017;Mills et al 2018;Mangilli et al 2019;Oka et al 2019) and theoretical (e.g. Kruijssen, Dale & Longmore 2015;Krumholz & Kruijssen 2015;Sormani, Binney & Magorrian 2015a, c;Krumholz, Kruijssen & Crocker 2017;Ridley et al 2017;Sormani et al 2018Sormani et al , 2019Armillotta et al 2019;Dale, Kruijssen & Longmore 2019;Kruijssen et al 2019a;Armillotta, Krumholz & Di Teodoro 2020;Li, Shen & Schive 2020) sides. Despite these advancements, many important open questions remain.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the rest of the CMZ clouds, the Brick is subjected to strong shear (𝑉/𝑅 ∼ 1.7 Myr −1 ; Kruijssen et al 2014; Krumholz lar clusters (Ginsburg & Kruijssen 2018). One explanation for the presently low SFR in the region is the idea that the CMZ undergoes bursts of star formation, followed by quiescent phases (Kruijssen et al 2014;Krumholz et al 2017;Armillotta et al 2020;Sormani et al 2020;Tress et al 2020). Longmore et al (2013b) and Barnes et al (2019Barnes et al ( , 2020 reported an increase of star formation activity as a function of orbital position angle among the subset of CMZ clouds known as the 'dust ridge' (which includes the Brick).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have performed simulations that follow the gas flow towards the galactic centre and connect kiloparsec scales to the inner few hundred parsecs (e.g. Sormani et al 2015;Armillotta et al 2019Armillotta et al , 2020Tress et al 2020;Sormani et al 2020). These simulations allow us to study the formation and large-scale properties of molecular clouds in the CMZ.…”
Section: Introductionmentioning
confidence: 99%